Incongruencia jurídica en el código de trabajo en relación al período de descanso de las personas que trabajan en servicio doméstico - Bonilla Logro, María Patricia (2015)
The present work of legal research, in order It Takes to amend Article 269 of the Ecuadorian Labor Code to a standard in Place to Ensure the rights established in the constitution so That people who work as domestic servants May enjoy two days off a week, this is Saturday and Sunday, According to the good life as the charter protection, so it is Intended to benefit, This segment of the population. This legal research is structured into six chapters. In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the proposed research. The second chapter refers to the theoretical framework, aspects: historical, doctrinal and legal. In the third chapter, the methodology used in the research described in question; the methods used the types of research, population, sample techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research results obtained through interviews with competent authorities based in the Canton La Maná, plus surveys of lawyers in professional free exercise, you know as they are violated without any consideration the rights of the people working in domestic service by those who are responsible for their hiring. The fifth chapter describes the conclusions and recommendations. Finally the sixth chapter discusses the proposal, objectives, description of' propuest, beneficiaries and social impact, etc.